Fungsi Corporate Social Responsibility Disclosure dan Independent Commissioning: Relevancy Of Accounting Information - Pratama, Maylady Nanda (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam UIN Sunan Ampel Surabaya, 2020)
This research specifically aims to determine the moderating effect of CSR disclosure on the relevance of earnings value and book value. In addition, this study also aims to prove the different effects of CSR disclosure moderation on the relevance of earnings and book values ??in companies that have and do not have an independent board of commissioners. In this journal the accounting information reviewed includes the value of earnings and book value. Profit is the information in financial statements that is most often used by investors in company valuations. Book value is very important and cannot be ignored in measuring the relevance of earnings. Accounting information is said to have value relevance if the accounting information can be used to predict the market value of the company. In addition, this study also examines the differences in the effect of CSR exposure on earnings and book values ??for companies that have Independent commissioning and companies that do not have Independent commissioning. Non-financial information that also plays a role in value relevance is a corporate governance mechanism. The corporate governance mechanism adopted by the company includes establishing an independent board of commissioners. The test results show that earnings and book values ??have value relevance. The moderating effect of CSR disclosure on the relevance of earnings and book values ??shows that CSR disclosure decreases the relevance of earnings but increases the relevance of book values. From the results of the Chow test results indicate that there are differences in the CSR moderation coefficient on the relevance of earnings and book values ??in companies that do not have Independent commissioning. Key words: value relevance; earnings; book value; independent board of commissioners. ABSTRAK: Penelitian ini secara spesifik bertujuan untuk mengetahui efek moderasi pengungkapan CSR terhadap relevansi nilai laba dan nilai buku. Selain itu, penelitian ini juga bertujuan untuk membuktikan perbedaan efek moderasi pengungkapan CSR terhadap relevansi nilai laba dan nilai buku pada perusahaan yang memiliki dan tidak memiliki Dewan Komisaris Independen. Dalam jurnal ini informasi akuntansi yang dikaji meliputi nilai laba dan nilai buku. Laba merupakan informasi dalam laporan keuangan yang paling sering dipakai oleh para investor dalam penilaian perusahaan. Nilai buku sangatlah penting dan tidak dapat diabaikan dalam pengukuran relevansi nilai laba. Informasi akuntansi dikatakan memiliki relevansi nilai jika informasi akuntansi tersebut bisa digunakan untuk memprediksi nilai pasar perusahaan Selain itu Pada penelitian kali ini juga mengkaji perbedaan pengaruh pendedahan CSR terhadap nilai laba dan nilai buku untuk perusahaan yang memiliki independent commissioning dan perusahaan yang tidak memiliki independent commissioning. adapun Informasi non keuangan yang turut berperan dalam relevansi nilai adalah mekanisme corporate governance. Mekanisme corporate governance yang diterapkan oleh perusahaan antara lain adalah dengan membentuk dewan komisaris independen. Hasil pengujian menunjukkan bahwa laba dan nilai buku memiliki relevansi nilai. Efek moderasi pengungkapan CSR terhadap relevansi nilai laba dan nilai buku menunjukkan bahwa pengungkapan CSR menurunkan relevansi nilai laba namun meningkatkan relevansi nilai nilai buku. Dari hasil Hasil uji Chow menunjukkan bahwa terdapat perbedaan koefisien moderasi CSR terhadap relevansi nilai laba dan nilai buku pada perusahaan yang tidak memiliki Independent commissioning.